Analysis Of Organizational Culture And Work Environment On Employee Performance With Motivation As An Intervening Variable In The Disaster Management Agency Batu Bara Regency - Pratomo, Priyo; Hernawaty, Hernawaty; Rahayu, Sri (Journal of Management, Economic, and Accounting, 2026)
Employee performance is a key factor in supporting the effectiveness of public organizations, particularly the Regional Disaster Management Agency (BPBD) of Batu Bara Regency, which is required to work quickly, accurately, and responsively in providing disaster services. This study aims to analyze the influence of organizational culture and work environment on employee performance, as well as to examine the role of work motivation as an intervening variable. This study used a quantitative approach with a census method on 81 employees of the BPBD of Batu Bara Regency. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method. The results showed that organizational culture and work environment had a positive and significant effect on employee performance and work motivation. In addition, work motivation also had a positive and significant effect on employee performance. The indirect effect test proves that work motivation acts as an intervening variable in the relationship between organizational culture and work environment on employee performance. These findings confirm that strengthening organizational culture, creating a conducive work environment, and continuously improving work motivation are very important for improving the performance of BPBD employees in Batu Bara Regency.